2021
DOI: 10.3390/polym13234198
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Functional Biopolymer-Based Nanocomposites for Active Food Packaging Applications

Abstract: Polymeric nanocomposites have received significant attention in both scientific and industrial research in recent years. The demand for new methods of food preservation to ensure high-quality, healthy foods with an extended shelf life has increased. Packaging, a crucial feature of the food industry, plays a vital role in satisfying this demand. Polymeric nanocomposites exhibit remarkably improved packaging properties, including barrier properties, oxygen impermeability, solvent resistance, moisture permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 169 publications
0
28
0
Order By: Relevance
“…or inhibit their entry and therefore this area of research is increasing the attention of the scientific community ( Khezerlou et al, 2018 ). In this context, nanocomposites play a pivotal role due to their barrier and antimicrobial properties ( Basavegowda and Baek 2021 ). Due to the application of antimicrobial agents and nanoparticles such as AgNPs, CuNPs, etc.…”
Section: Bioactive Nanocoating For Smart Nanoactive Packagingmentioning
confidence: 99%
“…or inhibit their entry and therefore this area of research is increasing the attention of the scientific community ( Khezerlou et al, 2018 ). In this context, nanocomposites play a pivotal role due to their barrier and antimicrobial properties ( Basavegowda and Baek 2021 ). Due to the application of antimicrobial agents and nanoparticles such as AgNPs, CuNPs, etc.…”
Section: Bioactive Nanocoating For Smart Nanoactive Packagingmentioning
confidence: 99%
“…Blending starch with other biopolymers such as chitosan [ 149 ], gelatin [ 150 ], polyvinyl alcohol [ 149 ], amongst many others, the strength-supporting framework has been investigated to compensate for the starch-based films’ weak mechanical characteristics. Combining two or more polymers yields novel materials with improved mechanical and gas barrier qualities, a viable replacement for synthetic food packaging materials [ 151 ]. Starch has traditionally been used as a food ingredient, but it is also being employed in a variety of other uses, including in the manufacture of aerogels and biofoams [ 19 ], paper, medicines, and textiles [ 152 ].…”
Section: Recent Trends Of Starch As Biopolymermentioning
confidence: 99%
“…Tong et al reported the glycerol addition to reduce the tensile strength and water barrier properties along with increase in the elongation at break and water solubility. 59 While studying the effect of various plasticisers and cross-linkers on extruded films, decrease in ultimate tensile strength on addition of glycerol plasticiser F I G U R E 3 Broad classification of biopolymers 26,29,44,[46][47][48] T A B L E 1 Types and origin of different biopolymers 4,26,29,44,[49][50][51][52][53] Types and origin of different biopolymers and derivatives…”
Section: Plasticisers and Cross-linking Agents For Biopolymersmentioning
confidence: 99%